THE APPLICATION OF IZIIGRID IN FACILITATING STUDENTS’ MASTERY OF THE GEOGRAPHIC GRID AMONG IN MALAYSIAN SECONDARY EDUCATION - Ali Hussein, Norlyziah (PEOPLE: International Journal of Social Sciences, 2019)
The goal of this study was to examine the effectiveness of an innovative teaching material known as “IziiGrid” in enabling students to master geographic grid which was one of the most important topics that students at the age of 15 in secondary school. The study was conducted on an intact class of 20 students at a secondary school in KK Sabah. The teaching material “IziiGrid” was designed from two rulers embedded with patterns that allowed students to locate geographic grid on a map or globe precisely. The students were taught on how to use this material and their performance was evaluated through pre-test and post-test. The results showed that all 20 students improved their performance by achieving the highest grade in the post-test when initially 19 of them failed the test prior to the intervention. The findings implied that ‘IziiGrid” is effective in facilitating students’ mastery of geographic grid and deepen their understanding of its importance. Thus, this innovation can be used widely to teach this topic.